Implementasi Demokrasi dalam Otonomi Desa - M Nur Budiyanto (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2002)
The village social and political development nowdays tend to show in the uncertain condition and mistrack. On one side, in the rural community there is much basic weakness such as the low degree of human resource, natural resource, culture, financial, and political and the economic infrastructure. The commitment of elite leadership (Village Legislative Body , Head of Village and its personnel) tend to be weak hear the village community aspiration. On other side, the centralgovernment (including localgovernment) articulate that the decentralisation process, democrag and village autonomy is also show the mistrack The attempt to impelement tightly the legislation of the village autonomy that must be obeyed and the legislation homogeni# for at least a district/ city is dearly the betrayal" to nature of autonomy itself. In such condition so the short term attempt that could be immediately done to reduce the problem is to make arrangement (sense straighting), consciuosness, and the political empowerment both for the village community and the central and local government. In addition, the misperception and unconciousness on decentralization, democrag and the village autonomy could be done 6y understanding the decentralization, democrag and the village community active participation in the real meaning that become the main pole of decentralization success and village autonomy. This writing contains the strategic management and suplementary and barrier factors in impelementing the village autonomy. Then as a anticipative attempt to reduce of unlimited and irresponsible freedom impact, anarcparticipation, and not respect the humanity aspect.